Microcantilever investigation of slow crack growth and crack healing in aluminium oxide - Jiang, J; Falco, S; Wang, S; Giuliani, F; Todd, RI (Elsevier, 2024)
Slow crack growth (SCG) plays an important role in the fracture of ceramics and glasses. A full understanding of the long term reliability of ceramic components therefore requires knowledge not only of fracture toughness (Kc) but also characteristics of SCG such as the threshold stress intensity factor (K0) of individual microstructural features. Previous investigations have been limited by the small scale of the microstructure and low crack growth rates involved. Here, the stress intensity factors for crack propagation Kp in sapphire were measured continuously under stable crack growth using chevron-notched microcantilevers, in air and in vacuum. Kp in vacuum was considered close to the fracture toughness Kc, with a value of 2.8 ± 0.1 MPa m1/2 for the a-plane of sapphire. Kp in air at 54 % relative humidity was reduced substantially by moisture-assisted SCG to around 1.7 MPa m1/2 and, with crack velocities of ∼20 nm/s, was considered to be close to K0. Cyclic loading in vacuum enabled quantitative measurements to be made during repeated crack growth and healing for the first time. Cracks healed up along their full length when unloaded but exhibited severe degradation of toughness on reloading. The toughness fell from 2.8 MPa m1/2 on the a-plane of pristine sapphire to 1.6 MPa m1/2 after one healing cycle and to successively lower values after further cycles. This technique offers a powerful method of investigating SCG and crack healing at the microstructural scale in different environments, with greater accuracy and on shorter timescales than can be achieved in macroscopic tests.